The Relationship between Workplace Stress with Burnout and Quality of Work Life among Managers and Staffs of the University of Medical Sciences (with an Emphasizing on the Mediating Role of Job Burnout and Workplace Stress) - Motie 1, Mahjoobe; Balaghat 1*, Seyed Reza (Shahroud Journal of Medical Sciences, 2018)
Background: This study was designed to examine the relationship between workplace stress and burnout and the quality of work life.Methods: This was a descriptive-surveying study with a correlational approach. The sample included managers and staff were selected by a census method based on the Morgan table and a total of 300 male and female employees were chosen through a stratified random sampling methodology using Morgan table. We used the Jagdish job stress questionnaire to measure the levels of job stress, while the burnout rate was assessed through Volfar job burnout scale. The Elena's quality of work life inventory was also applied to evaluate the quality of work life of the employees and managers.Results: We studied 352 samples. The mean age of the participants was equal to 32±3 years. There was a positive relationship between workplace stress and job burnout (P<0.01, r=0.31). A negative relation was also found between the workplace stress and quality of life (P<0.01, r=-0.62). Accordingly, the job burnout can reduce the quality of work life (P<0.01, r=-0.39). The mean value of the job stress of female managers and employees (66.69) was higher than male managers and employees (68.14), but the difference was not significant (P>0.05, df=350, t=2.03).Conclusions: The results did not confirm the mediatory role of job burnout in the correlation between job stress and quality of work life; however, a significant mediatory role of the stress was found and confirmed in the relationship between burnout and quality of work life.